BNIP3 expression in follicular lymphoma. - Sington, J; Giatromanolaki, A; Campo, L; Turley, H; Pezzella, F; Gatter, K (2007)
AIMS: To investigate the role of BNIP3, a 19-kDa interacting protein of the Bcl-2 family, alongside Bcl-2 in follicular lymphoma in comparison with reactive lymphoid hyperplasia. The results were compared with those from p53 and caspase-3 (apoptotic markers) and Ki67 (proliferation marker). METHODS AND RESULTS: Immunohistochemistry using monoclonal antibodies showed BNIP3 to be strongly expressed in most follicular lymphomas but to be weak to negative in all of the reactive cases. There was also an inverse relationship with Bcl-2 expression. There was no correlation of BNIP3 immunoreactivity with proliferation and caspase and p53 were virtually negative in all follicular lymphomas and reactive lymphoid cases. CONCLUSIONS: BNIP3 is strongly expressed in most follicular lymphomas, especially those that are Bcl-2 negative. BNIP3 may serve as a marker of more aggressive behaviour in follicular lymphoma and be useful diagnostically in the distinction from reactive lymphadenitis.